Design Of A Coconut Shell Charcoal Briquette Mixer Machine With A Capacity Of 50kg - Asep Rachmat; Gilang dwi Saputra; Alwi Albaar (Universitas Majalengka, 2026)
Coconut shell waste has not been optimally utilized, despite its potential to be processed into charcoal briquettes with higher economic value. One of the critical stages in briquette production is the mixing process, which requires an efficient and reliable mixing system to ensure homogeneity. This study aims to design a coconut shell charcoal briquette mixer machine with a capacity of 50 kg. The design methodology includes determining the mixer drum capacity, frame dimensions, and shaft specifications, followed by mechanical analysis to evaluate the torsional load acting on the shaft. Simulation analysis was conducted to assess the structural performance of the machine. The results indicate that the maximum stress due to torsional loading is 1.714 × 10⁵ Pa, while the resulting deformation is 3.306 × 10⁻⁵ m. These results demonstrate that the designed mixer machine meets the required safety criteria and is capable of operating effectively in the briquette mixing process. The proposed design is expected to improve efficiency and consistency in coconut shell charcoal briquette production.